Acute response to hydrotherapy after a simulated game of rugby - Higgins, T. R.; Cameron, M. L.; Climstein, M. (The Journal of Strength and Conditioning Research, 2013)
Despite lacking clear scientific evidence, hydrotherapies (water treatments) are accepted techniques to help team sport athletes recover from the physical effects of games. The purpose of this study was to assess the comparative effectiveness of cold water immersions (CWIs) and hot-and-cold contrast baths on athletes' recovery after a simulated game of rugby union. Twenty-four experienced, well-trained, male rugby union players were divided into 3 groups to receive recovery interventions: CWI for 1 group, contrast baths for a second group, and passive recovery for a third (control) group. Pregame and postgame measurements included a countermovement jump (normalized as a ratio to body weight), a sit-and-stretch flexibility test (centimeters), thigh circumference (to detect swelling; centimeters), and participants' perception of delayed-onset muscular soreness (DOMS, 100-mm visual analog scale). Statistical analysis included analysis of variance, and the calculation of omnibus effect sizes for each group () and the magnitudes of change within and between groups (Cohen's d). The participants in the contrast bath group reported statistically significantly greater measures of DOMS than participants in the control group did at 1 hour postintervention (p = 0.05, control group: d = 1.80; contrast bath: d = 4.75), and than participants in the CWI group did at 48 hours postintervention (p = 0.02, CWI: d = 1.17; contrast bath: d = 1.97). These findings provide modest evidence that contrast baths are a less effective strategy for recovery from rugby union than are CWI or passive recovery. Specifically, 2 × 5-minute CWI is superior to both contrasts baths and passive recovery in alleviating DOMS after exercise-induced muscle damage. Our recommendation for rugby union players aiming to attenuate the effects of DOMS postgames is to take 2 × 5-minute CWIs baths immediately after the game.